2000
DOI: 10.1111/j.1741-3737.2000.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspectives on Family Studies

Abstract: This article explores the relationship of historical research to contemporary family studies. Family history was influenced greatly by fields such as sociology and anthropology, leading it to make several contributions to those fields in turn. The continuing collaboration of these disciplines can significantly enrich current family research, practice, and policy making. History's specific contribution lies in its attention to context. Although historical research confirms sociologic and ethnographic findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 53 publications
(43 reference statements)
1
54
0
1
Order By: Relevance
“…By contrast, at present a larger number of co-resident extended families would embody just a tiny fraction of potential multigenerational households. For the same token, the privacy that is greatly valued by nuclear families today is fairly recent as in the earlier days it was quite common for servants, borders, lodgers to move freely in and out of the household and for more distant family members to visit (Ruggles 1994;Coontz 2000).…”
Section: How Demographic Factors Influences Household Structu Resmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, at present a larger number of co-resident extended families would embody just a tiny fraction of potential multigenerational households. For the same token, the privacy that is greatly valued by nuclear families today is fairly recent as in the earlier days it was quite common for servants, borders, lodgers to move freely in and out of the household and for more distant family members to visit (Ruggles 1994;Coontz 2000).…”
Section: How Demographic Factors Influences Household Structu Resmentioning
confidence: 99%
“…Indeed, later research demonstrated that there had indeed been a decline of extended families (Coontz 2000), although as a result of high mortality rates and second marriages, step-families were much more numerous than we today suppose (Segalen 1981;Coontz 2005). However, the explanation given was that as lives were shorter in the past, comparatively few families had had enough living members to potentially reside as a multigenerational household, but the ones that did represented a high proportion of all such potential arrangements.…”
Section: How Demographic Factors Influences Household Structu Resmentioning
confidence: 99%
See 3 more Smart Citations